2007
DOI: 10.1145/1250727.1250729
|View full text |Cite
|
Sign up to set email alerts
|

A study of thread migration in temperature-constrained multicores

Abstract: Temperature has become an important constraint in high-performance processors, especially multicores. Thread migration will be essential to exploit the full potential of future thermally constrained multicores. We propose and study a thread migration method that maximizes performance under a temperature constraint, while minimizing the number of migrations and ensuring fairness between threads. We show that thread migration brings important performance gains and that it is most effective during the first tens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…The second one is this argument should be used in trip count calculation and the argument should repeat. We report only on qualifying benchmarks, since others practically show neither speedup nor slowdown: hmmer and sphinx3 benchmarks from SPEC CPU 2006 benchmark suite, equake benchmark from SPEC OMP 2001 benchmark suite [2] and ATMI [13].…”
Section: A Experimental Set-upmentioning
confidence: 99%
“…The second one is this argument should be used in trip count calculation and the argument should repeat. We report only on qualifying benchmarks, since others practically show neither speedup nor slowdown: hmmer and sphinx3 benchmarks from SPEC CPU 2006 benchmark suite, equake benchmark from SPEC OMP 2001 benchmark suite [2] and ATMI [13].…”
Section: A Experimental Set-upmentioning
confidence: 99%
“…They showed that for four cores CMP running five threads, heat-and-run thread assignment (HRTA) and heat-and-run thread migration (HRTM) achieve 9% higher average throughput than stop-go and 6% higher average throughput than DVS. Moreover, when performance is constrained by temperature, the performance gains brought by thread migration and the importance of limiting the migration frequency to reduce performance overhead has been confirmed in [9]. In [9], a new migration method for temperature-constrained multicore is proposed to exchange threads whenever the simultaneous occurrence of a cold and a hot core is detected.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, when performance is constrained by temperature, the performance gains brought by thread migration and the importance of limiting the migration frequency to reduce performance overhead has been confirmed in [9]. In [9], a new migration method for temperature-constrained multicore is proposed to exchange threads whenever the simultaneous occurrence of a cold and a hot core is detected. The authors demonstrate that their method yields the same throughput with HRTM, but requires much less migrations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…All these techniques aim to ensure the system running under a fixed safe temperature constraint [2], [3], [5], [6], [7], [8],Most of these existing techniques is centralized approaches.…”
Section: Introductionmentioning
confidence: 99%